2006
DOI: 10.1159/000094869
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Docetaxel (Taxotere<sup>®</sup>) Used as a Single Agent and in Combination with Radiation in Human Gastric, Cervical and Pancreatic Cancer Cells

Abstract: Background: Docetaxel (Taxotere®) has gained increasing attention in clinical applications. We investigated the cytotoxic and radiosensitizing potential of docetaxel at nanomolar concentrations in six cell lines derived from tumors that rarely respond to radiation or chemotherapy, with special consideration of mechanisms of resistance, including the p53 mutational status. Methods: Cells derived from carcinomas of the human stomach (p53 mutant Hs746T, p53 wild type AGS), cervix (p53 wild type CaSki, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 100 publications
0
27
0
Order By: Relevance
“…In patients who achieved CR and/or PR, the median survival was 12.5 months (95% CI 8. [8][9][10][11][12][13][14][15][16].2) and the 1-year survival rate was 57%, with a median duration of response of 8 months.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In patients who achieved CR and/or PR, the median survival was 12.5 months (95% CI 8. [8][9][10][11][12][13][14][15][16].2) and the 1-year survival rate was 57%, with a median duration of response of 8 months.…”
Section: Resultsmentioning
confidence: 98%
“…Docetaxel has shown antitumor activity against a variety of cancers in clinical studies, such as head and neck, lung, gastric and breast cancer [14][15][16] . In a recent phase II clinical trial, single-agent docetaxel showed a partial response in 20% of patients with metastatic esophageal cancer [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The mutation rate of the former was 50–80% and that of the latter 33–67% [19]. Balcer-Kubiczek et al [20] investigated the cytotoxicity of docetaxel (Taxotere) used as a single agent and in combination with radiation in human gastric, cervical and pancreatic cancer cells. They found that the combination of isoeffective concentrations of docetaxel with graded X-ray did result in either a moderate synergy or in additivity.…”
Section: Discussionmentioning
confidence: 99%
“…Another important result, which is depicted in figure 4 , is that paclitaxel, which is used as an active agent against tumor cells of different origins [17] , inhibited the growth of MG-63 cells via cell cycle arrest at the S and G2/M stage. Paclitaxel may also prevent spindle formation of MG-63 cells and arrest cells in G2/M phase.…”
Section: Discussionmentioning
confidence: 99%